PENGARUH LEVERAGE, KEPEMILIKAN INTITUSIONAL, KARAKTER EKSEKUTIF, DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE - Erlina Sandya Prabawati; Arif Nugroho Rachman (Juremi: Jurnal Riset Ekonomi, 2022)
The research objective is to analyze the effect of leverage, institutional ownership, executive character, and company size on tax avoidance. The object in the research conducted is a food and beverage company that is listed on the Indonesia Stock Exchange (IDX) in 2017-2020. The source of the data usage is secondary data. The research population is 30 companies by analyzing financial statements from 2017-2020 which are accessed on the website, IDXnamely: www.idx.co.id . The sampling technique used was a purposive sampling technique where the research sample consisted of 16 companies. The data analysis techniques consist of descriptive statistical test, classical assumption test, multiple linear regression test, T test, F test, and determinant coefficient test (R2). According to the results of his research,variables leverage and institutional ownership have no effect on tax avoidance, executive character variables and company size have a significant effect on tax avoidance.